2022
DOI: 10.2196/36996
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Telemedicine Efficiency in Follow-up Care With Video Consultations for Patients in Orthopedic and Trauma Surgery in Germany: Randomized Controlled Trial

Abstract: Background Telemedicine can help mitigate important health care challenges, such as demographic changes and the current COVID-19 pandemic, in high-income countries such as Germany. It gives physicians and patients the opportunity to interact via video consultations, regardless of their location, thus offering cost and time savings for both sides. Objective We aimed to investigate whether telemedicine can be implemented efficiently in the follow-up care … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 35 publications
0
14
0
Order By: Relevance
“…This theme encompassed anxiety, well-being, stress, loneliness, depression, fear, personal satisfaction, helplessness, rumination, acceptance, suicidal ideation, and resilience. There were 13% (12/92) of instances of improved medical engagement [ 28 , 30 , 32 , 35 , 36 , 40 , 43 , 46 , 48 , 60 ]. This theme included medication compliance, program or treatment adherence, follow-up visits, medical knowledge, and decrease in emergency department visits.…”
Section: Resultsmentioning
confidence: 99%
“…This theme encompassed anxiety, well-being, stress, loneliness, depression, fear, personal satisfaction, helplessness, rumination, acceptance, suicidal ideation, and resilience. There were 13% (12/92) of instances of improved medical engagement [ 28 , 30 , 32 , 35 , 36 , 40 , 43 , 46 , 48 , 60 ]. This theme included medication compliance, program or treatment adherence, follow-up visits, medical knowledge, and decrease in emergency department visits.…”
Section: Resultsmentioning
confidence: 99%
“…The use of digital applications could be promoted in the form of apps or telemedicine when suited for the respective examinations. During the COVID-19 pandemic, the use of telemedicine has increased in many areas, such as outpatient care in general medical practices or follow-up care of surgery patients, often providing satisfactory results (Knörr et al 2022 ; Muschol et al 2022 ). Some cancer screenings have also been supported by telehealth services (Price et al 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…These questionnaires included questions about the distance between the patients' homes and the clinic, the amount of time spent for the appointment (eg, travel and waiting time), and the potential need to be absent from work to attend the appointment. Further information on the study can be found in a previous publication by Muschol et al [13].…”
Section: Course Of the Studymentioning
confidence: 99%
“…Various studies show that these goals can be achieved by introducing telemedicine in orthopedic and trauma surgery [6][7][8][9][10][11][12]. In addition, we have extensively analyzed patient and physician satisfaction, as well as quality of care for the study cohort in a previous publication [13]. Second, the costs of the technological infrastructure for telemedicine (eg, for electricity, internet connection, and hardware, such as computers and laptops with cameras and microphones) have to be considered.…”
Section: Implications For Practicementioning
confidence: 99%
See 1 more Smart Citation